1983
DOI: 10.1148/radiology.148.3.6308709
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer detected during a screening program using four-month chest radiographs.

Abstract: Ninety-two lung cancers were detected in the Mayo Lung Project in patients undergoing chest radiography every four months for screening. Fifty patients had a peripheral nodule, 16 had a perihilar nodule, 20 had hilar or mediastinal enlargement, and six had pneumonitis. The peripheral cancers grew slowly. Ninety per cent were visible in retrospect for months or even years. Despite this, 70% of the peripheral cancers were classified as postsurgical American Joint Committee (AJC) Stage 1. The central cancers grew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
9

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(155 citation statements)
references
References 0 publications
3
143
0
9
Order By: Relevance
“…Presumably, these tumours grew from a size that was below the resolution of the CT scan (1 -2 mm) to a readily detectable size in the interval. In the previous NCI chest X-ray screening studies, it was also observed that even with 4-monthly chest radiograph, 20% of the lung cancers were not visible in the prior examination (Muhm et al, 1983;Heelan et al, 1984). Thus, some lung cancers are rapidly growing, thereby escaping early detection and leading to the occurrence of symptomatic interval cancers in a screening programme.…”
Section: Tumour Growth Ratementioning
confidence: 99%
“…Presumably, these tumours grew from a size that was below the resolution of the CT scan (1 -2 mm) to a readily detectable size in the interval. In the previous NCI chest X-ray screening studies, it was also observed that even with 4-monthly chest radiograph, 20% of the lung cancers were not visible in the prior examination (Muhm et al, 1983;Heelan et al, 1984). Thus, some lung cancers are rapidly growing, thereby escaping early detection and leading to the occurrence of symptomatic interval cancers in a screening programme.…”
Section: Tumour Growth Ratementioning
confidence: 99%
“…Early detection of lung tumors (visible on the chest film as nodules) may greatly increase the patient's chance of survival. Strikingly, retrospective studies showed that 90% of peripheral lung cancers were visible on earlier radiographs [186]. Therefore this problem has received a lot of attention and is the most studied problem in computer analysis of chest radiographs.…”
Section: Nodule Detectionmentioning
confidence: 99%
“…Radiografias do tórax vs. tomografia computadorizada helicoidal (51)(52)(53)(54)(55)(56) : Os estudos realizados no passado demonstraram as limitações da radiografia do tórax na identificação precoce de nódulos pulmonares. No Mayo Lung Project, em uma análise retrospectiva, 90% dos carcinomas periféricos e 75% dos peri-hilares, já estavam presentes em radiografias anteriores (51) .…”
Section: Problemas Metodológicos E Principais Limitações Dos Protocolunclassified
“…No Mayo Lung Project, em uma análise retrospectiva, 90% dos carcinomas periféricos e 75% dos peri-hilares, já estavam presentes em radiografias anteriores (51) . Quekel et al (52) demonstraram que 19% dos casos de carcinomas perifé-ricos escaparam à identificação radiológica (diâmetro médio de 16mm).…”
Section: Problemas Metodológicos E Principais Limitações Dos Protocolunclassified